Spinal myeloid sarcoma presenting as initial symptom in acute promyelocytic leukemia with a rare cryptic PLZF::RARα fusion gene: a case report and literature review - Zhang, Xuejiao; Wang, Tao; Chen, Pu; Chen, Yan; Wang, Zhimei; Xu, Tianhong; Yu, Pengfei; Liu, Peng (Frontiers in Oncology, 2024)
Background: Acute promyelocytic leukemia (APL) is rarely caused by the PLZF::RARα fusion gene. While APL patients with PLZF::RARα fusion commonly exhibit diverse hematologic symptoms, the presentation of myeloid sarcoma (MS) as an initial manifestation is infrequent.A 61-year-old patient was referred to our hospital with 6-month history of low back pain and difficulty walking. Before this admission, spine magnetic resonance imaging (MRI) conducted at another hospital revealed multiple abnormal signals in the left iliac bone and vertebral bodies spanning the thoracic (T11-T12), lumbar (L1-L4), and sacral (S1/S3) regions. This led to a provisional diagnosis of bone tumors with an unknown cause.On admission, complete blood count (CBC) test and peripheral blood smear revealed a slightly increased counts of monocytes. Immunohistochemical staining of both spinal and bone marrow (BM) biopsy revealed positive expression for CD117, myeloperoxidase (MPO), and lysozyme. BM aspirate showed a significant elevation in the percentage of promyelocytes (21%), which were morphologically characterized by round nuclei and hypergranular cytoplasm. Multiparameter flow cytometry of BM aspirate revealed that blasts were positive for CD13, CD33, CD117, and MPO. Through the integrated application of chromosome analysis, fluorescence in situ hybridization (FISH), reverse transcriptase polymerase chain reaction (RT-PCR), and Sanger sequencing, it was determined that the patient possessed a normal karyotype and a rare cryptic PLZF::RARα fusion gene, confirming the diagnosis of APL.In the present study, we report the clinical features and outcome of a rare APL patient characterized by a cryptic PLZF::RARα fusion and spinal myeloid sarcoma (MS) as the initial presenting symptom. Our study not only offers valuable insights into the heterogeneity of APL clinical manifestations but also emphasizes the crucial need to promptly consider the potential link between APL and MS for ensuring a timely diagnosis and personalized treatments.